Analytical theory of one- and two-dimensional hard sphere fluids in random porous media - Holovko, M.F.; Shmotolokha, V.I.; Dong, W. (Condensed Matter Physics, 2010)
The recently proposed scaled particle theory SPT2 approach to the description of three-dimensional hard sphere fluids in random porous media is extended for one- and two-dimensional cases. Analytical expressions for the chemical potential and pressure of one- and two-dimensional hard sphere fluids in hard sphere and overlapping hard sphere matrices are obtained and discussed. Some improvements and modifications of the obtained results are proposed. Недавно запропоновану теорію масштабної частинки SPT2 для опису тривимірного плину твердих сфер у випадковому пористому середовищі узагальнено на одно- та двовимірні випадки. Одержано та розглянуто аналітичні вирази для хімічного потенціалу та тиску одно- та двовимірних твердих сфер у матрицях твердих сфер і твердих сфер, що перетинаються. Запропоновано деякі покращання та модифікації одержаних результатів. We thank T. Patsahan for some interesting discussions. The support from the CNRS-NASU cooperation project is acknowledged.